Prognostic potential of neutrophil-to-lymphocyte ratio and lymphocyte nadir in stage III non-small-cell lung cancer. (July 2017) - Kang, Kylie H; Efird, Jimmy T; Sharma, Neelesh; Yang, Michael; Dowlati, Afshin; Linden, Philip; Machtay, Mitchell; Biswas, Tithi
Aim: Studies have shown increased pretreatment neutrophil-to-lymphocyte and platelet-to-lymphocyte ratios to be predictive of survival in various cancers. Our aim was to evaluate the prognostic role of such inflammatory markers in non-small-cell lung cancer (NSCLC).Methods: One hundred and sixty-three patients with stage III NSCLC who received definitive treatment were included. Survival analysis was performed using Kaplan–Meier method. Hazard ratios for overall and recurrence-free survival were estimated using Cox proportional hazards model.Results: Both neutrophil-to-lymphocyte >Q75 (4.5) and lymphocyte nadir values <Q25 (0.25) and their unified values were associated with 90% increased overall mortality risk (p = 0.040) and a nonsignificant 50% decreased recurrence-free survival risk.Conclusion: Our exploratory analysis showed markers of systemic inflammation predicted survival outcomes in advanced NSCLC. Future prospective data analyses are needed to confirm this potential.